(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Teacher professional development (TPD) is essential for enhancing pedagogical practices and improving educational outcomes. This paper examines the relationship between TPD and pedagogical practices, exploring how professional development initiatives influence teachers’ instructional methods and student achievement. Through a review of existing literature and analysis of key TPD programs, this paper highlights the critical elements of effective professional development and its impact on teaching quality. A case study analysis further illustrates the application of these principles in real-world educational settings.